Unplugged Activity and Cognitive Style on The Speaking Abilities of Early Children - Setyo Dewi, Yuli Ani; Degeng, I Nyoman Sudana; Cahyono, Bambang Yudi; Ulfa, Saida; Sailaja, S. V. (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
The ability to speak well and purposefully must be instilled in children from an early age. This is possible through the learning process at school using interesting learning methods and media according to the child's cognitive style. Because spoken language conveyed through speaking is a tool for expressing thoughts and feelings and a means of communication between humans. This will help improve children's speaking ability. This research aims to determine the differences in speaking abilities between students using the unplugged activity method and those using the beyond center and circle times (BCCT). Determine the differences in speaking ability between students with a field-dependence cognitive style and those with a field-independence cognitive style. The researcher tests the interaction between learning methods and cognitive style regarding speaking ability. This research uses an experimental design. The subjects were PGRI Jambon Kindergarten students (TK B1) and (TK B2) who studied the theme of Animals, totaling 44 children. The cognitive style was measured using a questionnaire based on the Children Embedded Figure Test (CEFT). Data analysis of relationships and interactions between variables used the two-way ANOVA test. The research results show that differences influence speaking ability between students using unplugged activity learning and BCCT. Some differences influence the student’s speaking abilities with a field-independence cognitive style and those with a field-dependence cognitive style. There is an interaction between learning methods and cognitive style regarding speaking ability.